Do commodity price volatilities impact currency misalignments in commodity-exporting countries? - Boubakri, Salem (2020)
This paper aims to investigate the relationship between misalignments of real effective exchange rates and real commodity price volatilities in a sample of 46 commodity-exporting countries by considering financial development as the transition variable. We first estimate currency misalignments as deviations of the observed real effective exchange rates from their equilibrium values estimated using the behavioural equilibrium exchange rate (BEER) approach. Then, we rely on panel data and a smooth-transition regression model to estimate commodity price volatilities' non-linear impacts on currency misalignments. Our results indicate that the estimated coefficients are highly significant, and demonstrate that real commodity prices' volatility has a non-linear impact on currency misalignments depending on the country's degree of financial development.